Comparative Audit of Batam City Information System and COVID-19 National Website - Hendi Sama; Muhammad Rivaldy Hisham; Jumiliono Pratama; Luky Andito; Andy Kho; Hendry Wijaya (Universitas Negeri Medan, 2022)
The use of Information Technology for the information center on the COVID-19 web in Batam city and the COVID-19 web in Indonesia, must be supported by IT Governance which describes the most important factors in the use of IT. In addition, the development of the internet also supports the use of computers. The data on the two websites may still not be used as the main reference data due to differences in data from the national web version and Batam City, also because the data obtained are not aligned and do not intersect, it can cause errors in reporting the data that has been collected in such a way. In this study, an Information System Audit will be carried out with the process of collecting and also evaluating evidence about the accuracy of the available information to determine the level of suitability of the information with the audit standards that have been set and express the results of the examination, based on the information system audit standards. The results of the assessment of aspects of the security system, design, navigation, mobile friendly, speed, content quality and keywords of the two websites show that it is very worthy to say that it is very good.